A multi-agent knowledge expert locating system: A software agent simulation on personal knowledge management (PKM) model - Ismail S.; Nguyen T.D.; Ahmad M.S. (IEEE Computer Society, 2023)
This paper presents a multi-agent simulation that demonstrates personal knowledge management (PKM) processes among knowledge workers based on a PKM model. Two scenarios are simulated: the mediation of Knowledge Seeker-Knowledge Expert and Knowledge Seeker-Knowledge Collaborator tasks that are animated in an agent-oriented development platform. The results of the simulation validate the PKM model at agent-mediation level. © 2013 IEEE.